Development of an Acehnese Value-Based Education Implementation Model at SMK Negeri 7 - Taufiq, Taufiq; Siraj, Siraj; Nasrah, Sayni (Malikussaleh University, Aceh, Indonesia, 2022)
The values of Islamic character should be the spirit that colors all aspects of education, both in classroom-based learning, the climate of school life, as well as in the context of interaction with community life in general, integrated into learning starting from planning, implementing, and evaluating according to the characteristics Basic Competence. Learning in vocational schools needs to be designed according to the demands of the curriculum in an effort to instill Acehnese values through production-based training/production-based education and training and Islamic edutechnopreneur learning practices. The objectives of this research are to: 1) Develop a model of education implementation based on Acehnese values through the Islamic Edutechnopreneur model; 2) Testing the quality of the education delivery model; and 3) Analyzing teacher and student responses to the Acehnese values-based education model through the Islamic Edutechnopreneur model that has been developed at SMK Negeri 7 Lhokseumawe. This study uses the Research and Â Development method. The importance of this research is because vocational and school teachers really need a model of Islamic edutechnopreneur-based education and its implementation in school life. The results showed that the success of the Edutechnopreneur production unit at SMK Negeri 7 Lhokseumawe really depends on the management applied in the school. Therefore, it is important to strengthen SMK management so that Islamic Edutechnopreneur production units can be developed in an effort to strengthen the competitiveness of graduates. Teachers are an important resource, involve teachers in various trainings that enable them to develop in mastery of competencies and achieve increased insight and entrepreneurial skills.